Multisynchronization for Coupled Multistable Fractional-Order Neural Networks via Impulsive Control - Jin-E Zhang (Complexity)
We show that every subnetwork of a class of coupled fractional-order neural networks consisting of N identical subnetworks can have r+1n locally Mittag-Leffler stable equilibria. In addition, we give some algebraic criteria for ascertaining the static multisynchronization of coupled fractional-order neural networks with fixed and switching topologies, respectively. The obtained theoretical results characterize multisynchronization feature for multistable control systems. Two numerical examples are given to verify the superiority of the proposed results.